Oh, East is East, and West is West, and Never the Two Shall Meet: A Critical Review of Museum Studies and Adult Education Literature - Dana Dudzinska-Prezesmitzki; Robin S. Grenier (Adult Education Research Conference, 2008)
Both museum and adult learning researchers seek to understand how to best educate adults. Despite a plethora of common areas where the two fields intersect this review found limited evidence of shared epistemological, theoretical and empirical research or “roots”. Given the mutual interests of these fields it is argued that sharing of epistemological, theoretical and empirical research would benefit both. Implications and future research opportunities are discussed.
Keywords: museums; adult learning; literature review